(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
Translation equivalence has long served as one of the central concepts in translation studies, yet its theoretical interpretation has evolved significantly over the past century. This article examines modern perspectives on translation equivalence by reviewing key theoretical developments, identifying shifts from formal to functional models, and exploring how equivalence is reconceptualized within pragmatics, corpus linguistics and cognitive translation studies.